1996
DOI: 10.1111/j.1468-2958.1996.tb00377.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Cultural Individualism-Collectivism, Self Construals, and Individual Values on Communication Styles Across Cultures

Abstract: Individualism-collectivism has a direct effect on communication styles and an indirect effect that is mediuted through self construals and values. It was hypothesized that cultural individualism-collectivism, self construals, and values would haw separate effects on individuals' use of low-and high-context communication styles. As predicted, the results ofthis study suggest that independent self construals and individualistic values mediate the influence of cultural individualism-collectivism on the use of low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
745
2
10

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 855 publications
(784 citation statements)
references
References 44 publications
27
745
2
10
Order By: Relevance
“…The relevance of situation descriptions in SJTs may be contingent on the cultural background of individuals, insofar as some cultures may be better able "to fill in the blanks" (the missing situation descriptions) than other cultures. For instance, crosscultural research has demonstrated that cultures may either be high or low on context (Gudykunst et al, 1996;Hall, 1976;Kittler, Rygl, & Mackinnon, 2011). Similarly, individuals from either universalistic or particularistic cultures may show differences in their tendency to apply general domain knowledge.…”
Section: Limitationsmentioning
confidence: 99%
“…The relevance of situation descriptions in SJTs may be contingent on the cultural background of individuals, insofar as some cultures may be better able "to fill in the blanks" (the missing situation descriptions) than other cultures. For instance, crosscultural research has demonstrated that cultures may either be high or low on context (Gudykunst et al, 1996;Hall, 1976;Kittler, Rygl, & Mackinnon, 2011). Similarly, individuals from either universalistic or particularistic cultures may show differences in their tendency to apply general domain knowledge.…”
Section: Limitationsmentioning
confidence: 99%
“…Although the mediation of individual-level measures of individualism versus collectivism and its related construct, independent versus interdependent self-construals (Gudykunst, Matsumoto, & Ting-Toomey, 1996;Singelis, 1994), have been successfully documented to some degree (Lam & Zane, 2004;Singelis, Bond, Sharkey, & Lai, 1999;Uskul, Hynie, & Lalonde, 2004), they certainly do not account for all cultural differences in cognition, emotion, and motivation. This is partly because predicted relationships between countries and independent and interdependent self-construalsespecially between the United States and Japan, which serves as a comparison in so many studies-have not always been supported by data (Matsumoto, 1999(Matsumoto, , 2002Oyserman, Coon, & Kemmelmeier, 2002;Takano & Osaka, 1999), or they have failed to correlate with the dependent variables (Chang, Arkin, Leong, Chan, & Leung, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Collectivism, on the other hand, grants priority to group identity over individual identity, shared in-group beliefs over unique individual beliefs, and cooperation with in-group members over maximizing individual outcomes (see Gudykunst et al 1996). Triandis (1988) states that members of individualist cultures are characterized by hedonism and self-seeking attitudes, suggesting weak bonds to society.…”
Section: Collectivism-indivisualismmentioning
confidence: 99%
“…Indeed, cross-cultural scholars posit that members of collectivist cultures, such as Japan's, tend to place a higher value on family, family relationships, and on relationships with others in the society, while members of individualistic cultures, such as America's, tend to place a higher value on independence and autonomy (see Gudykunst et al 1996;Hofstede 1980Hofstede , 1984Hofstede , 1991Hofstede , 2001Matsumoto and Juang 2004;Matsumoto et al 1996Matsumoto et al , 1997Triandis 1988Triandis , 1999. In other words, using Hirschi's (1969) terminology, we might argue that members of collectivist cultures are more strongly attached to parents, peers, teachers, and schools.…”
Section: Collectivism-indivisualismmentioning
confidence: 99%
See 1 more Smart Citation